1998
DOI: 10.1046/j.1365-201x.1998.0400e.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac accumulation of citrate during brief myocardial ischaemia and reperfusion in the pig in vivo

Abstract: Citrate is a key intermediate in energy metabolism and an inhibitor of phosphofructokinase of the glycolytic pathway. During myocardial ischaemia glycolysis is the main source of cardiac ATP. The aim of the present study was to determine if myocardial ischaemia and reperfusion alter cardiac tissue levels of citrate. Open-chest, anaesthetized pigs were subjected to 10 min of regional myocardial ischaemia by occlusion of the left anterior descending coronary artery, with and without reperfusion, and to 10 min of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Increased iron-dependent toxicity due to citrate may explain the observation that biochemical parameters of damage in mouse cardiomyocytes occur before histochemically measurable iron accumulation (2). Much of the tissue damage in ischemia-reperfusion injury also is due to increased cytosolic iron, because iron chelation reduces tissue pathology (39)(40)(41), but during ischemia reperfusion there is also a 4-to 6-fold increase in citrate (42). Our results suggest that the combination of iron and citrate promotes tissue injury.…”
Section: Discussionmentioning
confidence: 64%
“…Increased iron-dependent toxicity due to citrate may explain the observation that biochemical parameters of damage in mouse cardiomyocytes occur before histochemically measurable iron accumulation (2). Much of the tissue damage in ischemia-reperfusion injury also is due to increased cytosolic iron, because iron chelation reduces tissue pathology (39)(40)(41), but during ischemia reperfusion there is also a 4-to 6-fold increase in citrate (42). Our results suggest that the combination of iron and citrate promotes tissue injury.…”
Section: Discussionmentioning
confidence: 64%
“…Finally, metabolite changes observed in humans modulated the response to hypoxic injury in vitro, which suggests that these metabolites not only serve as markers, but may also modulate the evolving response to ischemia in vivo. The metabolic, structural, and functional consequences of ischemia and/or reperfusion have been examined in a wide variety of experimental animal models, including regional ischemia after coronary vessel occlusion in dogs (29)(30)(31) and swine (32)(33)(34)(35) as well as in humans with coronary disease (36)(37)(38)(39)(40) or undergoing heart surgery (41-43). However, prior studies have generally assayed relatively limited subsets of metabolites in focused approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary occlusion in an in vivo porcine model resulted in an abrupt 60% to 70% increase in myocardial citric acid content. 21 Furthermore, by cannulating the anterior interventricular vein in an in vivo porcine model, Panchal et al 22 demonstrated that an abrupt decrease in left anterior descending coronary artery flow resulted in an 80% decrease in citric acid efflux from the myocardium. These data support the notion that the metabolic changes that we observed are a direct consequence of myocardial ischemia and extend prior studies by their direct application to humans.…”
Section: Functional Pathway Analysismentioning
confidence: 99%